Evolutionary Relationships Between Low Potential Ferredoxin and Flavodoxin Electron Carriers - Campbell, Ian J.; Bennett, George N.; Silberg, Jonathan J. (Frontiers in Energy Research, 2019)
Proteins from the ferredoxin (Fd) and flavodoxin (Fld) families function as low potential electrical transfer hubs in cells, at times mediating electron transfer between overlapping sets of oxidoreductases. To better understand protein electron carrier (PEC) use across the domains of life, we evaluated the distribution of genes encoding [4Fe-4S] Fd, [2Fe-2S] Fd, and Fld electron carriers in over seven thousand organisms. Our analysis targeted genes encoding small PEC genes encoding proteins having ≤200 residues. We find that the average number of small PEC genes per Archaea ( 13), Bacteria ( 8), and Eukarya ( 3) genome varies, with some organisms containing as many as 54 total PEC genes. Organisms fall into three groups, including those lacking genes encoding low potential PECs (3%), specialists with a single PEC gene type (20%), and generalists that utilize multiple PEC types (77%). Mapping PEC gene usage onto an evolutionary tree highlights the prevalence of [4Fe-4S] Fds in ancient organisms that are deeply rooted, the expansion of [2Fe-2S] Fds with the advent of photosynthesis and a concomitant decrease in [4Fe-4S] Fds, and the expansion of Flds in organisms that inhabit low-iron host environments. Surprisingly, [4Fe-4S] Fds present a similar abundance in aerobes as [2Fe-2S] Fds. This bioinformatic study highlights understudied PECs whose structure, stability, and partner specificity should be further characterized.